2014
DOI: 10.1007/s00253-014-5878-1
|View full text |Cite
|
Sign up to set email alerts
|

GlnR-mediated regulation of nitrogen metabolism in the actinomycete Saccharopolyspora erythraea

Abstract: Nitrogen source sensing, uptake, and assimilation are central for growth and development of microorganisms which requires the participation of a global control of nitrogen metabolism-associated genes at the transcriptional level. In soil-dwelling antibiotic-producing actinomycetes, this role is played by GlnR, an OmpR family regulator. In this work, we demonstrate that SACE_7101 is the ortholog of actinomycetes' GlnR global regulators in the erythromycin producer Saccharopolyspora erythraea. Indeed, the chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 22 publications
1
73
0
Order By: Relevance
“…The MEME/MAST tools (http://meme -suite.org/) and the PREDetector software program were used to identify GlnR and PhoP binding sites in the upstream region of glucosidase-encoding genes in S. erythraea NRRL23338. The training set of sequences used to generate weight matrices and prediction methods has previously been described (34,35,41).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MEME/MAST tools (http://meme -suite.org/) and the PREDetector software program were used to identify GlnR and PhoP binding sites in the upstream region of glucosidase-encoding genes in S. erythraea NRRL23338. The training set of sequences used to generate weight matrices and prediction methods has previously been described (34,35,41).…”
Section: Methodsmentioning
confidence: 99%
“…The gene knockout strategy was described in our previous study (34). Briefly, the glnR mutant was generated by protoplast transformation with pUC-glnR (Table 1), replacing the 771 bp of the glnR open reading frame (SACE_7101) with a thiostrepton (tsr) resistance cassette.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GlnR regulon has been determined and includes at least 15 genes that encode proteins (mainly enzymes) involved in nitrogen source uptake and signal sensing (the amtB-glnK-glnD operon), alternative nitrogen source utilization (nirB, nasA, and ureA) and glutamine/glutamate synthesis (glnA, glnII, and gdhA) (6). The role of GlnR has also been investigated in other actinomycetes, including Streptomyces venezuelae (8), Amycolatopsis mediterranei (9), and Saccharopolyspora erythraea (10), among others. For instance, in S. venezuelae, a genome-wide analysis by chromatin immunoprecipitation (ChIP) assay coupled with microarray analysis (ChIP-chip) was performed and revealed the presence of 36 GlnR-binding sites, mainly located upstream of genes involved in nitrogen metabolism (8).…”
mentioning
confidence: 99%
“…S2; ref. 23), and GlnR has been shown to regulate their expression (24). We found that two GS enzymes, GSI-β GlnA1 and GSII GlnA4, were directly acetylated in vitro after incubation with AcuA and AcCoA; AcuA did not acetylate GlnA2 or GlnA3 ( Fig.…”
Section: Resultsmentioning
confidence: 70%